Influence of TiO2 nanoparticles on the performance and inner structure of zein/eugenol films. (March 2022) - Xiao, F.H.; Wang, J.; Wang, D.G.; Zhai, J.Q.; Lu, G.X.; Chen, C.Z.
Abstract: Zein/eug/TiO2 composite films were prepared by casting method at reaction temperature of 80 ℃ and drying temperature of 70 ℃ . In order to investigate the influence of TiO2 nanoparticles on the performance and microstructure of zein/eug films, the surface and cross-section morphologies, functional groups, tensile properties, barrier properties, hydrophobicity and thermal stability were studied by SEM, FTIR, and comprehensive analysis of the experimental results dealt by origin. Results showed that the tensile strength of composites have been improved up to 64.04% with 1 wt% TiO2 nanoparticles compared with the control sample. The thermal stability, barrier properties (water vapor permeability and oxygen permeability) have been improved to varying degrees after loading different amounts of TiO2 nanoparticles as result of microstructure with different reduction on size and numbers of clusters and cavities. Furthermore, no significant differences were found associated to antibacterial properties among samples with and without TiO2 nanoparticles. In addition, SEM images showed the surface and cross-section structures with lower porosity explaining for the enhancement of inner structure. Basically similar wavenumbers and intensities of all the peak in FTIR spectra illustrated that TiO2 nanoparticles were regarded as the physical connections in the polymer matrix. Highlights: The numbers of holes in composites reduced by adding TiO2 . The addition of TiO2 nanoparticles improved the tensile strength and barrier properties. TiO2 made use of physical connection between itself and polymer matrix to improve the tensile strength and barrier properties.